Reaksi Pasar Atas Stock Split Pada Emiten Saham Syariah di Bursa Efek Indonesia Periode 2011-2014 - Jasmine, Aldila Vania; Herlambang, Leo (Jurnal Ekonomi Syariah Teori dan Terapan, 2015)
The aims of this study are to identify and explain the market reaction as the result of corporate action in the form of stock split managed by the stock issuers registered with Jakarta Islamic Index and Indonesia Sharia Stock Index from period 2011 to 2014.This study used quantitative approach with event study method. Those stock issuers also have to perform the stock split and have been registered with ISII and JII to fulfill the requirements of this study. While the focus of this study is the reaction indicated by the change of AAR and CAAR by doing several test such as one sample t-test and paired sample t-test by defining the level of significant in the amount of 5%.The results of the study indicate there is no significance difference in the AAR before and after the stock split, but there is a quite significance difference in the CAAR.